SIMULATION OF CHANGE IN PERFORMANCE INDICATORS (NET PROFIT, LAND AREA, NUMBER OF EMPLOYEES) OF AGRICULTURAL COOPERATIVES OF UKRAINE - Diana SHELENKO; Ivan BALANIUK; Oleksandr SHPYKULIAK; Liudmyla SAS; Мariana HUMENIUK; Petrо MATKOVSKYI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the paper was to assess the potential opportunities for the development of agricultural cooperatives until 2030. The importance of modeling the forecast parameters of development in time to ensure the effective functioning of cooperatives was substantiated. It was found that the size of their net income is most affected by: the area of agricultural land, the number of enterprises, the number of employees and the total cost of production. A research using the STELLA program showed that the number of agricultural cooperatives will be reduced 13.1 times by 2030, according to the area of agricultural land they will decrease 1.5 times, and the amount of profits will increase significantly in contrast to losses. This is due to the processes of concentration of cooperative structures, automation of production and implementation of innovative technologies.